New palynological information from the subsurface Copo, Caburé and Rincón formations (upper Lochkovian-Emsian), Salta Province, Argentina - Noetinger, Maria Sol (2013)
New palynological information recovered from cutting and core samples from the Puesto El Tigre x-1 well in northwestern Argentina is presented. The studied interval corresponds to the Copo, Cabure and Rinc n formations. The assemblage comprises 41 spore and cryptospore species, 27 species of acritarchs together with prasinophycean and chlorophycean algae, and 12 chitinozoan species. The stratigraphic distribution of these taxa allow the definition of five associations, ranging in age from late Lochkovian to latest Emsian. These associations reflect palaeoenvironmental changes related to transgressive-regressive cycles occurring during this time span, which corroborates previous interpretations.